Gut microbiota and metabolome distinctive features in Parkinson disease: Focus on levodopa and levodopa‐carbidopa intrajejunal gel. (16th December 2020) - Melis, Marta; Vascellari, Sarah; Santoru, Maria Laura; Oppo, Valentina; Fabbri, Margherita; Sarchioto, Marianna; Murgia, Daniela; Zibetti, Maurizio; Lopiano, Leonardo; Serra, Alessandra; Palmas, Vanessa; Pisanu, Silvia; et al.
Abstract: Background and purpose: Recent data suggest that imbalances in the composition of the gut microbiota (GM) could exacerbate the progression of Parkinson disease (PD). The effects of levodopa (LD) have been poorly assessed, and those of LD‐carbidopa intestinal gel (LCIG) have not been evaluated so far. The aim of this study was to identify the effect of LD and LCIG, in particular, on the GM and metabolome. Methods: Fecal DNA samples from 107 patients with a clinical diagnosis of PD were analyzed by next‐generation sequencing of the V3 and V4 regions of the 16S rRNA gene. PD patients were classified in different groups: patients on LCIG (LCIG group, n  = 38) and on LD (LD group, n  = 46). We also included a group of patients ( n  = 23) without antiparkinsonian medicaments (Naïve group). Fecal metabolic extracts were evaluated by gas chromatography mass spectrometry. Results: The multivariate analysis showed a significantly higher abundance in the LCIG group of Enterobacteriaceae, Escherichia, and Serratia compared to the LD group. Compared to the Naïve group, the univariate analysis showed a reduction of Blautia and Lachnospirae in the LD group. Moreover, an increase of Proteobacteria, Enterobacteriaceae, and a reduction of Firmicutes, Lachnospiraceae, and Blautia was found in the LCIG group. No significant difference was found in the multivariate analysis of these comparisons. The LD group and LCIG group were associated with a metabolic profile linked to gut inflammation. Conclusions: Our results suggest that LD, and mostly LCIG, might significantly influence the microbiota composition and host/bacteria metabolism, acting as stressors in precipitating a specific inflammatory intestinal microenvironment, potentially related to the PD state and progression. Abstract : The aim of this study was to identify the effect of levodopa (LD) and, in particular, LD‐carbidopa intestinal gel (LCIG) on gut microbiota (GM) and metabolome in Parkinson disease patients. After correction for multiple confounders, we showed that LD, and mostly its intraduodenal injection (i.e., LCIG), might significantly influence GM composition, driving a metabolic dysregulation linked to a specific inflammatory gut microenvironment. The potential detrimental and proinflammatory effects mediated by antiparkinsonian medicaments on GM was also confirmed in our direct evaluation of fecal metabolites in the metabolome analysis, showing that the altered composition of the GM matched metabolic changes, mostly affecting lipids, fatty acids, polyamines, and metabolism of amino acids.